The Use of Logistic Performance Measures in the Sugar and Alcohol Sector: An Exploratory Case Study - Barbosa, Danilo Hisano; Herrera, Vânia Érica; Kurumoto, Juliana Sayuri; Musetti, Marcel Andreotti (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper presents part of a broader study performed by a research group in logistics, which evaluated the statusof an entire Supply chain, regarding the excellence of its logistic practices, using some excellence models as aconceptual background. Thus, the research problem consisted in finding out which logistic performance measuresfor the group of cost metrics; asset management; customer service and productivity are used by a xx sugarcaneplant. In order to answer that question, it was used the descriptive-exploratory research and the research strategybased on a case study, comparing the variables selected to investigation and the plant reality. The research resultsshowed that the plant is focused on costs and productivity metrics, with less attention to customer service andasset management. Furthermore, it was verified regarding the evaluation perspective a greater attention to aBenchmarking perspective, with less attention to the functional view and hardly any activities connected to theSupply chain perspective.Keywords: Logistics, Performance Measurement, Performance Measures, Sugarcane.